Effect of abiotic factors on viability and characterization of Metarhizium rileyi Nm017 (2019)
The species Chloridea virescens and Helicoverpa zea (Lepidoptera: Noctuidae) are declared agricultural pests with a high economic impact worldwide (Angulo et al. 2008). They are widely distributed on the American continent, and agrochemical are the most common method to control, which can cause environmental, social, economic and public impacts. A strain of Metarhizium rileyi Nm017 [AGROSAVIA - Orinoquia area (Col.)], demonstrated an e cacy of 75.8% on C. virescens, and 92.5% on H. zea on laboratory conditions. Mass production and virulence of Metarhizium sp. are susceptible to stress conditions such as temperature, UVB radiation and pH, a ecting conidial vigor, germination, and sporulation (Rangel et al. 2008, Oliveira et al. 2016). Likewise, the culture medium can a ect the infection processes measured through hydrophobicity and enzymatic activities (Ortiz 2013). The identi cation of these parameters allows selecting the most favorable conditions for its production and the challenges that must be assumed in downstream processes.